Unity in Embedded System Design and Robotics : A Step-by-Step Guide. - Moshayedi, Ata Jahangir; Kolahdooz, Amin; Liao, Liefa ([Place of publication not identified] : Chapman and Hall/CRC, 2022)
The first book of its kind, Unity in Embedded System Design and Robotics provides a step-by-step guide to Unity for embedded system design and robotics. It is an open gateway for anyone who wants to learn Unity through real projects and examples as well as a particularly useful aid for both professionals and students in the fields of embedded system design and robotics. Each chapter contains a unique project. The user is guided through the different windows and sections of Unity every step of the way. The book also includes projects that connect Unity to Arduino and Raspberry Pi, which will help readers better understand various Unity applications in the real world.
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY / Robotics; COMPUTERS / Computer Science; TECHNOLOGY / Automation; Unity (Electronic resource) -- Handbooks, manuals, etc; Virtual reality -- Computer programs -- Handbooks, manuals, etc; Three-dimensional modeling -- Handbooks, manuals, etc; Application software -- Development -- Handbooks, manuals, etc; Embedded computer systems -- Design and construction; Robotics